Historical perspectives supporting the ambitious anesthetist aiming for zero nausea/vomiting: should one trust every consensus statement every time? - Brian A. Williams; Brian A. Williams; Christopher A. Schumacher; Ridhi Choragudi; Kelly E. Garbelotti; John M. Ludden; Daniel E. Hall; Daniel E. Hall; Daniel E. Hall (Frontiers in Anesthesiology)
Within the domain of perioperative prophylaxis against postoperative nausea and/or vomiting (PONV), there seems to be (i) a consensus-guided “hard stop” recommendation after four prophylactic anti-emetic medications are utilized, and (ii) an assumption that each of the four “usual” PONV medications/categories produces 25% risk reduction from the “previous baseline”, representing a “law of diminishing returns.” Meanwhile, recently-described 5-medication PONV prophylaxis (palonosetron, perphenazine, aprepitant, dexamethasone, diphenhydramine) has been observed to achieve 90%–95% prophylaxis success, particularly in patients receiving intrathecal morphine (a known, potent emetogenic stimulus). This meaningful prevention thematically differs from the scholarly prevention benchmark that may be over-reliant on patient-specific preoperative risk factors, described in the 1990s and before, dictating prophylaxis strategies. Meaningful prevention with 5-medication PONV prophylaxis (which we recommend before entry into the operating theater) (i) may serve as a surprisingly effective antecedent to further avoid postoperative opioids, (ii) may be augmented throughout hospitalization and convalescence with daily “booster dosing”, and (iii) may (in combination with booster dosing) mitigate possible “rebound nausea” that has been reported by esteemed PONV thought leaders in the context of post-discharge nausea and/or vomiting. The described processes (pan-prophylaxis before emetic stimuli are incurred, antiemetic booster dosing, and potential downstream opioid reduction by enhancing adherence to postoperative oral/enteral non-opioid analgesic formulations) would seem to create a win-win scenario for patients and hospitals alike. The described antiemetic techniques remain compatible with available opioid-free anesthetic techniques [lidocaine, acetaminophen, N-methyl-D-aspartate (NMDA) antagonists, etc.]. Some perspectives shared herein may further inform as to how and why.